Paratriathlon race performance in elite ambulatory athletes with physical impairments - Bevins, R. L. (American Journal of Physical Medicine & Rehabilitation, 2024)
Objective The aim of this study was to compare overall performance and performance within the individual disciplines (e.g., swim) in elite paratriathlon between the ambulatory classes PTS2-5 in men and women.